The Effect of Adventure Video Games on the Development of Student’s Character and Behavior - Kristiadi, Dedy Prasetya; Hasanudin, Muhaimin; Sutrisno, Sutrisno; Suwarto, Suwarto (Universitas Malikussaleh, 2019)
The gaming world development and applications in information and communication technology are increasing in the digital era nowadays. Activities in video games can be a hobby or to fill your spare time. Games can be media education that contain learning orientation, skills and cooperation. Video games can also affect the behavior of special players and the environment in general. One type of video games that provides it, is adventure video games which are the result of combining survival methods for specific purposes that contain knowledge of the surrounding environment and skills in exploiting opportunities. The main player character is often presented in video games in the form of problem solving and thinking ability in complete the adventure or the game itself based on the character for the purpose of learning about characters that are strengthened with certain skills. Video games with the main character elements in them can reflect the discovery of new ideas, approval of ideas, completion of skills or reconfiguring ideas, so playing an adventure video game can lead to positive values that influence players' thought also motivate them to complete adventure challenges. In this study, we want to know the effect of adventure video games on the development of student’s character and behavior. From the calculation of the Wilcoxon test it can be concluded that; (1) adventure video games influence the development of student character (2) Adventure video games influence the development of student behavior.